Influence of contrasting cultivation altitudes on the physicochemical, digestive, and functional properties of four Musa starches produced in Cameroon - (:unkn) unknown (My University, 2024)
Source Agritrop Cirad (https://agritrop.cirad.fr/605069/) * Autres projets (id;sigle;titre): ;RTBfoods project;(FRA) Breeding RTB Products for End User Preferences//
Keywords: African Research